Gaps in science-policy interface: textual analysis of scientific insights overlooked by policies during COVID-19 - Ren Chao; Yang Menghui (Journal of Data and Information Science)
Policies have often, albeit inadvertently, overlooked certain scientific insights, especially in the handling of complex events. This study aims to systematically uncover and evaluate pivotal scientific insights that have been underrepresented in policy documents by leveraging extensive datasets from policy texts and scholarly publications.